Curie Temperature of Diluted Magnetic Semiconductors: the Influence of the Antiferromagnetic Exchange Interaction - Tuan, Hoang Anh; Thai, Vu Kim; Anh, Le Duc (Communications in Physics, 2012)
The coherent potential approximation and mean field approximation are used to calculate the free energy of the coupled carrier – localized spin system in III-V diluted magnetic semiconductors. Thus the magnetic transition temperature Tc can be determined and its dependence on important model parameters. We show that the strong antiferromagnetic superexchange interaction between nearest neighbour sites considerably reduces the Curie temperature.